2010
DOI: 10.2165/10061630-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Fenofibric Acid Co-Administered with Low- or Moderate-Dose Statin in Patients with Mixed Dyslipidemia and Type 2 Diabetes Mellitus

Abstract: Fenofibric acid + statin combination therapy in patients with mixed dyslipidemia and type 2 diabetes was well tolerated and resulted in more comprehensive improvement in the lipid/apolipoprotein profile than either monotherapy. [Clinical trials are registered at www.clinicaltrials.gov: NCT00300482, NCT00300456, and NCT00300469].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 32 publications
(40 reference statements)
1
21
0
3
Order By: Relevance
“…For example, a pooled subgroup analysis of three randomized, controlled, double-blind, 12-week trials that included 586 patients with mixed dyslipidemia and T2DM showed that the fenofibric acid/statin combination treatment was associated with a significantly greater improvement of lipid profile compared with either monotherapy [157]. Indeed, it was shown that the combination of fenofibric acid with low-or moderate-dose statin, led to a 5-fold higher percentage of patients achieving the combined optimal levels of LDL-C, non-HDL-C, apoB, TG and HDL-C [157].…”
Section: Effects Of Statin and Fibrate Combination On Metabolic Parammentioning
confidence: 99%
“…For example, a pooled subgroup analysis of three randomized, controlled, double-blind, 12-week trials that included 586 patients with mixed dyslipidemia and T2DM showed that the fenofibric acid/statin combination treatment was associated with a significantly greater improvement of lipid profile compared with either monotherapy [157]. Indeed, it was shown that the combination of fenofibric acid with low-or moderate-dose statin, led to a 5-fold higher percentage of patients achieving the combined optimal levels of LDL-C, non-HDL-C, apoB, TG and HDL-C [157].…”
Section: Effects Of Statin and Fibrate Combination On Metabolic Parammentioning
confidence: 99%
“…Several recent studies have demonstrated the efficacy and safety of fenofibric acid and statin therapy in patients with mixed dyslipidemia in reducing triglycerides and raising HDL-C compared with statin monotherapy. 37,38 NOVEL HDL THERAPIES This complex process involved in RCT provides multiple targets to modulate HDL metabolism with novel therapies. RCT involves the efflux of free cholesterol (FC) in the macrophage to discoidal pre-b1 HDL.…”
Section: Statin-niacin Combination Therapymentioning
confidence: 99%
“…Three statin medications have been tested: rosuvastatin, simvastatin, and atorvastatin. These trials found an added increase in HDL over that achieved with statin alone: 16 [21]. Enhanced reduction of triglycerides was also seen: 43.9% decrease (299.9 to 158.4 mg/dL [3.39 to 1.79 mmol/L]) with the statin/fenofibrate combination.…”
Section: Fibric Acid Derivatives Plus Statin Therapymentioning
confidence: 98%